Comparing the Accuracy of Hierarchical Agglomerative and K-means Clustering on Mobile Augmented Reality Usability Metrics - Cheng L.K.; Selamat A.; Zabil M.H.M.; Selamat M.H.; Alias R.A.; Puteh F.; Mohamed F.; Krejcar O. (Institute of Electrical and Electronics Engineers Inc., 2023)
Augmented reality; Big data; Hierarchical clustering; Learning systems; Machine learning; Usability engineering; Hierarchical agglomerative clustering; K-means; Performance metrics; Self-reported Metrics; Usability; K-means clustering